Handling Victims of Sexual Violence Against Children in the Criminal Justice System in Indonesia - Marlene Sualang; Noenik Soekorini; Syahrul Borman (Civiliza Publishing, 2026)
Sexual violence against children remains a serious and escalating problem in Indonesia, causing long-term physical, psychological, and social harm to victims. Children, as vulnerable individuals, often face difficulties in accessing justice due to fear, trauma, power imbalances, and inadequate institutional support. This study aims to analyze the handling of child victims of sexual violence within the Indonesian criminal justice system and to examine the forms of legal protection provided to them. This research employs a normative legal research method using a statutory and conceptual approach by examining relevant laws and regulations, including the Child Protection Law and Law Number 12 of 2022 on Sexual Violence Crimes. The results show that although the legal framework for protecting child victims has been strengthened, particularly through the enactment of the Sexual Violence Crimes Law, its implementation within the criminal justice system still faces significant challenges. These include limited victim-centered approaches, risks of re-victimization during legal proceedings, and insufficient coordination among law enforcement institutions. The study concludes that an effective handling of child victims of sexual violence requires an integrated, victim-oriented criminal justice system that prioritizes protection, recovery, and the best interests of the child.